Motor Vehicle Crash-Related Subdural Hematoma from Real-World Head Impact Data - Urban, Jillian E. (Mary Ann Liebert, Inc., 2012)
Approximately 1,700,000 people sustain a traumatic brain injury (TBI) each year and motor vehicle crashes (MVCs) are a leading cause of hospitalization from TBI. Acute subdural hematoma (SDH) is a common intracranial injury that occurs in MVCs associated with high mortality and morbidity rates. In this study, SDH volume and midline shift have been analyzed in order to better understand occupant injury by correlating them to crash and occupant parameters. Fifty-seven head computed tomography (CT) scans were selected from the Crash Injury Research Engineering Network (CIREN) with Abbreviated Injury Scale (AIS) level 3+ SDH. Semi-automated methods were used to isolate the intracranial volume. SDH and additional occupant intracranial injuries were segmented across axial CT images, providing a total SDH injury volume. SDH volume was correlated to crash parameters and occupant characteristics. Results show a positive correlation between SDH volume and crash severity in near-side and frontal crashes. Additionally, the location of the resulting hemorrhage varied by crash type. Those with greater SDH volumes had significantly lower Glasgow Coma Scale (GCS) scores at the crash site in near-side crashes. Age and fracture type were found to be significant contributors to SDH volume. This study is a volumetric analysis of real world brain injuries and known MVC impacts. The results of this study demonstrate a relationship among SDH volume, crash mechanics, and occupant characteristics that provide a better understanding of the injury mechanisms of MVC-associated TBI.